Cisa : certified information systems auditor study guide - Cannon, David (Wiley Publishing, 2011)
"The industry-leading study guide for the CISA exam, fully updated More than 27,000 IT professionals take the Certified Information Systems Auditor exam each year. SC Magazine lists the CISA as the top certification for security professionals. Compliances, regulations, and best practices for IS auditing are updated twice a year, and this is the most up-to-date book available to prepare aspiring CISAs for the next exam. CISAs are among the five highest-paid IT security professionals; more than 27,000 take the exam each year and the numbers are growing Standards are updated twice a year, and this book offers the most up-to-date coverage as well as the proven Sybex approach that breaks down the content, tasks, and knowledge areas of the exam to cover every detail. Covers the IS audit process, IT governance, systems and infrastructure lifecycle management, IT service delivery and support, protecting information assets, disaster recovery, and more. Anyone seeking Certified Information Systems Auditor status will be fully prepared for the exam with the detailed information and approach found in this book."--Provided by publisher